Metales traza en sedimentos costeros de Costa Rica Jairo - García-Céspedes, Jairo; Acuña-González, Jenaro; Vargas-Zamora, José A. (Revista de Biología Tropical, 2004)
Marine sediment samples from four coastal ecosystems in Costa Rica were taken between the years 2000-2002 and their iron, lead, copper and zinc concentrations were determined by the atomic absorption technique with flame or graphite furnace. In the Pacific coast, Culebra Bay (Papagayo Gulf), Gulf of Nicoya, and Golfito Bay (Dulce Gulf), were selected as representative sites, and Moín Bay, at the Caribbean coast. Mean metal concentrations for all ecosystems followed the same pattern: Fe > Zn > Cu > Pb. No temporal pattern was found for any metal. Iron and copper mean concentrations were higher in Golfito Bay (5.8% and 87 μg / g, respectively) and lower in Moín Bay (3.4% and 52 μg / g, respectively). Zinc mean concentration was also higher in Golfito Bay (96 μg / g), but lower in Culebra Bay (66 μg / g). Lead mean concentration was higher in Moín Bay (6.4 μg / g) and lower in Culebra Bay (3.0 μg / g). Lead highest concentrations occurred in the Caribbean and in Golfito Bay, and for the rest of the elements the maximum values were found in Golfito Bay. On the basis of data obtained in this work, Culebra Bay was considered a relatively unpolluted location; Golfito Bay was more contaminated, and Moín Bay and the Gulf of Nicoya showed an intermediate condition.